1996
DOI: 10.1515/hfsg.1996.50.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Residues and Extracts of High-Pressure Extraction of Eucalyptus Wood by 1,4-Dioxane-CO2 Mixtures. Part I. Characterisation by FTIR, UV and HPLC

Abstract: In this work residues and extracts resulting from high-pressure extractions of Eucalyptus globulus Labill. by 1,4-dioxane and l,4-dioxane-CO2 mixtures, in the temperature range 160°C-180°C at 170 bar and 250 bar pressures were characterised by spectroscopic and Chromatographie techniques. Spectral data of extraction residues showed that thermal degradation starts to occur at 180°C. At lower temperatures cellulose is neither degraded nor extracted and changes in intensity of FTIR absorption bands indicate ligni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The extent of delignification achieved in only 30 min reaction time for pulping of P. taeda is in the same order of magnitude reported in the literature for different solvent mixtures and wood species treated with longer reaction times [4,8,9,10].…”
Section: St Set: Effect Of the Reaction Timesupporting
confidence: 84%
See 1 more Smart Citation
“…The extent of delignification achieved in only 30 min reaction time for pulping of P. taeda is in the same order of magnitude reported in the literature for different solvent mixtures and wood species treated with longer reaction times [4,8,9,10].…”
Section: St Set: Effect Of the Reaction Timesupporting
confidence: 84%
“…Machado et al studied the reactive extraction of lignin from Eucalyptus globules sawdust with pure dioxane and dioxane-carbon dioxide mixtures at 170 bar and temperatures in the range of 160-180 • C and 300 min as reaction time [9,10]. In the experiments performed with pure dioxane the increase in the temperature produced small increase in the amount of hemicelluloses and lignin removal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of this technique for lignin extraction and cellulosic pulp production has been reported only in few published works [4][5][6][7][8][9][10]. These studies were performed employing organic solvents (acetic acid, ethanol, methanol, dioxane, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that pressure has an effect on the enzymatic hydrolysis of cotton fibre by using enzymes from Trichoderma viride in scCO 2 , increasing the reaction rate by 1.4 times when pressure was increased from 1 to 120 atm (Muratov 2007). Mixtures of dioxane -scCO 2 have been used by Reis Machado et al (1994Machado et al ( , 1996Machado et al ( , 1997 in the reactive extraction and characterisation of lignins from Eucalyptus globulus wood.…”
Section: Cellulose Reactions and Chemical Modifications In Sccomentioning
confidence: 99%